In vitro and in vivo studies on exogenous polyamines and α-difluoromethylornithine to enhance bone formation and suppress osteoclast differentiation - Chien-Ching Lee; Chia-Chun Chuang; Chung-Hwan Chen; Yuan-Pin Huang; Chiao-Yi Chang; Pei-Yi Tung; Mon-Juan Lee (Amino Acids)
Abstract Exogenous polyamines, including putrescine (PUT), spermidine (SPD), and spermine (SPM), and the irreversible inhibitor of the rate-limiting enzyme ornithine decarboxylase (ODC) of polyamine biosynthesis, α-difluoromethylornithine (DFMO), are implicated as stimulants for bone formation. We demonstrate in this study the osteogenic potential of exogenous polyamines and DFMO in human osteoblasts (hOBs), murine monocyte cell line RAW 264.7, and an ovariectomized rat model. The effect of polyamines and DFMO on hOBs and RAW 264.7 cells was studied by analyzing gene expression, alkaline phosphatase (ALP) activity, tartrate-resistant acid phosphatase (TRAP) activity, and matrix mineralization. Ovariectomized rats were treated with polyamines and DFMO and analyzed by micro computed tomography (micro CT). The mRNA level of the early onset genes of osteogenic differentiation, Runt-related transcription factor 2 (Runx2) and ALP, was significantly elevated in hOBs under osteogenic conditions, while both ALP activity and matrix mineralization were enhanced by exogenous polyamines and DFMO. Under osteoclastogenic conditions, the gene expression of both receptor activator of nuclear factor-κB (RANK) and nuclear factor of activated T-cells, cytoplasmic 1 (NFATc1) was reduced, and TRAP activity was suppressed by exogenous polyamines and DFMO in RAW 264.7 cells. In an osteoporotic animal model of ovariectomized rats, SPM and DFMO were found to improve bone volume in rat femurs, while trabecular thickness was increased in all treatment groups. Results from this study provide in vitro and in vivo evidence indicating that polyamines and DFMO act as stimulants for bone formation, and their osteogenic effect may be associated with the suppression of osteoclastogenesis.